Design of transport and launch system for a portable robot system - Neo, Zheng Jing (Nanyang Technological University, 2021)
For a portable robot system to arrive to its designated site location to carry out its task, a proper transportation and launching system will be required. Therefore, in this report, the main focus is on the understanding and implementation of current available mechanisms that can be found in the market. In this report, the targeted portable robot system is a laser material deposition system, which will be used for maintenance of railway tracks. There have been previous reports made discussing the use of laser material deposition for maintenance of railway tracks and crossing. Therefore, in this report, for the transport system, road-rail vehicle mechanism will be implemented to ensure that the device holding the portable robot system is capable in traversing on both road and railway tracks. For the launch system, working mechanisms such as Hiab Crane, Electric Jib, Liftgate and Skip Loader are discussed and analysis for both the loading and unloading of the portable robot system. With the Skip Loader having the highest loading and unloading capacity, while also being the most compact mechanism. Since the launch mechanisms discussed are market products, models made following their product specifications would be feasible in carrying out the launching task. Future work is to implement automated guided vehicle as the base of the portable robot system, to reduce the need for the present of an operator on site for maintenance.